Linoleic Acid Blocks the Inhibitory Effects of Caffeine on Tumour Promotion by 12-O-Tetradecanoylphorbol-13-Acetate in Two-Stage Carcinogenesis in Mouse Skin - Ken Yasukawa, (Journal of Pharmacy and Nutrition Sciences, 2015)
The present study assessed the in vivo effects of fatty acids on inflammation and carcinogenesis in mice. Fifteen fatty acids were examined for their effects on the inhibitory effect of caffeine on 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced ear oedema in mice. Furthermore, linoleic acid was studied for its effects on the inhibitory effect of caffeine on carcinogenesis in mouse skin initiated with 7,12-dimethylbenz[a]anthracene (DMBA) and promoted by TPA. Among fatty acids, linoleic, γ-linolenic and oleic acids most strongly blocked the inhibitory effect of caffeine on TPA-induced ear oedema. Furthermore, linoleic acid also markedly blocked the inhibitory effect of caffeine on the tumour-promoting activity of TPA. This is the first report to suggest that fatty acids, such as linoleic, γ-linolenic and oleic acids, block the anti-inflammatory activity of caffeine on TPA-induced inflammation in mice. Linoleic acid blocked the inhibitory effect of caffeine on tumour promotion by TPA in the two-stage mouse skin carcinogenesis model. These results suggest that intake of linoleic acid requires attention.